2023
DOI: 10.1186/s41232-023-00277-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Alzheimer’s disease: microglial signature and their relevance to disease

Abstract: Alzheimer’s disease (AD) is the most common form of dementia, pathologically characterized by senile plaques and neurofibrillary tangles (NFTs), resulting in neurodegeneration. Neuroinflammation, defined as the activation of glial cells such as microglia and astrocytes, is observed surrounding senile plaques and affected neurons in AD. Recently conducted genome-wide association studies (GWAS) indicate that a large section of identified AD risk genes are involved in immune responses and are enriched in microgli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 43 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…In AD treatment, MSCs are often used as a regenerative medicine to differentiate into neurons or Schwann cell-like cells [ 62 ]. It has been suggested that neuroinflammation triggered by activated microglial cells plays a key role in the pathogenesis of AD [ 63 ]. Moreover, it is well-known that IL-10 deficiency exacerbates inflammation-induced tau pathology [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In AD treatment, MSCs are often used as a regenerative medicine to differentiate into neurons or Schwann cell-like cells [ 62 ]. It has been suggested that neuroinflammation triggered by activated microglial cells plays a key role in the pathogenesis of AD [ 63 ]. Moreover, it is well-known that IL-10 deficiency exacerbates inflammation-induced tau pathology [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative diseases associated with neuroinflammation encompass a category of diseases that affect the spinal cord and the brain resulting in progressive degeneration of neural tissue and mortality (Sobue et al, 2023). In these diseases, there is a release of immune cells into the CNS causing inflammation and resulting in the degeneration of the neural tissues.…”
Section: Neurodegenerative Disease Associated With Neuroinflammationmentioning
confidence: 99%
“…AD is marked by a continuous degenerative process, initially presenting with memory impairment, and subsequently leading to cognitive decline that can affect behavior, language, visuospatial orientation, and ultimately the motor system. As shown in Figure 2, the neuropathological characteristics of AD include extracellular Aβ(amyloid beta) plaques and intracellular hyperphosphorylated tau (p-τ) forming neurofibrillary tangles, accompanied by synaptic and neuronal loss (Sobue et al, 2023). Neuroinflammation in AD occurs when glial cells, mainly microglia and astrocytes, get activated.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Though these are the widely accepted causes of AD, there are various hypotheses in understanding AD pathology which targets several mechanisms mainly Aβ-induced neurotoxicity, tau pathogenesis, and neuroinflammatory pathways. The heterogeneous nature of AD complicates its diagnosis, prognosis, treatment, and drug design.…”
Section: Introductionmentioning
confidence: 99%